The experience of EU countries towards the development of infrastructure and logistics hubs - Slatvinska, Valeria; Kibik, Olha; Oneshko, Svitlana; Fesak, Serhii (Journal of the University of Zulia, 2022)
The objective of the study is to assess the development of infrastructure and logistics hubs using the example of the EU countries, namely: Germany, Spain and Poland. The methodology is based on a comparative analysis of infrastructure hubs development indicators in Germany, Spain and Poland according to InfraCompass. Results. The general policy and strategy of the EU as a supranational institution determines the strategic goals and policies of Germany, Spain, and Poland in the field of infrastructure and logistics development. The EU provides financial incentives, political and administrative support for infrastructure hubs and logistics. Based on the research results, Germany, Spain, and Poland have common strengths contributing to infrastructure development: fair and transparent public procurement, a good insolvency protection system (Germany and Poland), a high credit rating (Germany), and financial stability (Poland). The general factors of the infrastructure facilities development are: in Germany – the development of infrastructure hubs is ensured by an effective regulatory framework and established rules for permitting, a quality legal system, a stable financial sector; in Spain – effective regulatory framework, effective tools of public administration; in Poland – the regulatory framework and infrastructure management systems.